Pengaruh Auditor’s Professional Skepticism, Red Flags, Beban Kerja Pada Kemampuan Auditor dalam Mendeteksi Fraud - Purwanti, I Gusti Ayu Putu Della Sabrina; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 21 No 2 (2017)DO - 10.24843/EJA.2017.v21.i02.p11, 2017)
The development of the world economy has never escaped the existence of fraud committed by some companies. Some companies take advantage of this opportunity to expand the company's economic sector, as well as achieve huge profits in a fast way just to create a good corporate image in the eyes of the public or investors. The company will conduct fraud with one of the ways of manipulating the recording of financial statements. Problems arise when the rampant cases of fraud involving public accounting firm to make people began to doubt the ability of auditors in detecting fraud. This study aims to determine the effect of auditor’s professional skepticism, red flags, and workload on the auditor's ability to detect fraud. This research was conducted in 6 KAP with sample of 40 respondents, using non probability sampling method. Data were collected by distributing questionnaires using 5 Likert scale points to measure 45 indicators, using multiple linear regression analysis techniques. The results of the study found that auditor's professional skepticism and red flags positively influence the auditor's ability to detect fraud. Workload negatively affects the auditor's ability to detect fraud. It is concluded that auditor's professional skepticism and red flags can improve auditor's ability to detect fraud, while workload can decrease the auditor's ability to detect fraud.